Nonsedated Magnetic Resonance Imaging for Congenital Sensorineural Hearing Loss - Cheng, Jeffrey; Nguyen, Vinh (Journal of Pediatric Neuroradiology, 2015)
Hearing loss is the most common congenital condition in the United States. Magnetic resonance imaging (MRI) may be used in evaluation. Imaging in infants and children often requires sedation or general anesthesia to acquire images not degraded by motion artifact. Avoidance of sedation may decrease resource utilization and potentially avoid not yet understood possible cognitive deficits from early anesthetic exposure.Given that the membranous labyrinth, cochlea, and internal auditory canal are normally high in fluid concentration, an MRI focused on T2 imaging at the beginning of the study may provide an alternative imaging strategy with avoidance of anesthesia and radiation.
Keywords: congenital; sensorineural hearing loss; magnetic resonance